ANALISA TOPIK TERHADAP KOMENTAR MENGENAI METAVERSE MENGGUNAKAN METODE CLUSTERING K-MEANS - Andre Ertanto; Viny Christanti Mawardi; Novario Jaya Perdana (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
The development of the internet doesn't stop there, but continues to develop and evolve, even in a game, humans can interact with each other, make transactions with each other and maybe it becomes an opportunity to earn income, one that combines all of these things is known as the Metaverse. Metaverse is a layer that connects two worlds, namely: the real world and the virtual world. Metaverse offers a 3-dimensional experience that can be shared between users and interact within this technology where every activity of its users can be carried out with the help of Augmented and Virtual Reality technology services. In the metaverse, people want to see what topics are contained in the discussion. So a website was created to determine the topic of metaverse comments from social media. The method used on this website is Clustering K-means. Use this method to divide comments into groups that have something in common. The group of comments will be determined by the topic of the highest frequency of words. Evaluation uses the Elbow Method to determine the optimal k value in Clustering K-means.